Decomposition of carbon emission influencing factors and research on emission reduction performance of energy consumption in China - Xiao, Min; Peng, Xingzhi (Frontiers in Environmental Science, 2023)
In recent years, global warming has become increasingly prominent, and energy conservation and emission reduction have become an important direction of national industrial development. In order to promote the effective promotion of China's carbon emission reduction action, the research uses the improved STIRPAT model and Granger test to analyze the factors affecting China's energy consumption carbon emissions, and combines the Johan equation and GFI decomposition to decompose the factors affecting China's energy consumption carbon emissions, excavate the key influencing conditions for China's energy consumption carbon emissions, and propose policy recommendations for energy consumption carbon emissions reduction. The research results show that economic growth has the highest impact on China's per capita carbon emissions, followed by urbanization, industrial structure and energy structure. Industrial energy intensity has a restraining effect on per capita carbon emissions growth. From 2019 to 2021, Shanghai, Tianjin, Guangdong and other 10 provinces will achieve good emission reduction results. The research on the decomposition and analysis of the influencing factors of China's energy consumption carbon emissions can provide direction and guidance for exploring an effective low-carbon development path, and play an important role in promoting the realization of the "dual carbon" goal.